Slavoj Zizek : a critical introduction - Parker, Ian, 1956- (Modern European thinkers., 2004)
This work shows the reader a clear path through the twists and turns of Slavoj Žižek's writings. Ian Parker takes his treatment of Hegel, Lacan and Marx in turn and assesses Žižek's interpretation and extension of these thinkers' theories.